Sonification of Deproteinized Bovine Bone Functionalized with Genistein Enhances Bone Repair in Peri-Implant Bone Defects in Ovariectomized Rats - Duarte, Nathália Dantas [UNESP] (2024)
Estrogen deficiency is one of several contributing factors to catabolic changes in bone surrounding dental implants, impairing bone repair in defects requiring bone regeneration. Functionalizing bone substitutes is an alternative approach among various strategies to address this challenge. In this study, the aim was to evaluate the effect of functionalizing deproteinized bovine bone (Bio-Oss®, BO) with genistein via sonication on peri-implant bone defects in ovariectomized rats. The animals were randomly distributed according to the treatment into the following four groups (n = 10): BO sonicated with genistein (BOS + GEN), BO sonicated alone (BOS), untreated BO (BO), and blood clot only (CLOT). After twenty-eight days, implant removal torque was determined, and the peri-implant bone parameters were calculated based on computed microtomography. Additionally, the gene expression of bone turnover markers was evaluated. As a main result, the functionalization with genistein increased implant removal torque and the peri-implant bone volume in the BOS + GEN group compared to both BOS and BO groups (both p < 0.05). These findings suggest that the sonification of deproteinized bovine bone functionalized with genistein improves bone repair in peri-implant bone defects in ovariectomized rats.